The Interaction Effect of Urea and Super Phosphate Fertilizer on the Nutritional Status of Wheat Plant (Triticum aestivum L.) - Al-Shamary, M. Z. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A pots experiment was conducted in the plastic house of Kalar Horticulture station Province of Sulaimania, by using soil brought from one of Kalar region fields during growing season of 2007-2008, to study the effect of increasing levels of urea fertilizer which is (0, 0.20,0.40,0.80) g/pot which equals to (0,100,200,400) kg urea/ha, and super phosphate fertilizer which is (0,0.24,0.48)gm/pot which is equal (0,120,240) kg sup/ha, in nutrition state of wheat IPA 95 component, clay determining Nitrogen, Phosphor and Potassium content in green part and seeds. The Completely Randomized Design was used with three replication per treatment combination. Results showed increasing content nuteriant elements in green part and seed with increasing level of the studied fertilizers.